Impact Of High-Intensity Interval Training on Specific Physical Factors Among College Men Ball Badminton Players - M., Ezhilarasan; Ali Khan D. J., Asath; S., Sivarani (Journal of Neonatal Surgery, 2025)
Examining how high-intensity interval training affected particular physical characteristics in collegiate men's ball badminton players was the goal of this study. Thirty individuals, ages 18 to 24, were selected at random from SRM Institute of Technology, Kattankulathur, in order to accomplish this purpose. A control group and an experimental group, each with 15 participants, were subsequently randomized to these chosen individuals. The control group did not participate in any experimental activities, whereas the experimental group trained using high-intensity intervals. This study concentrated on two aspects of physical fitness: muscle strength and agility. Both pre-tests and post-tests were part of the genuine random group design used in the research. Each of the 30 participants was split equally between the control group and the experimental group, which included the interval training at high intensity group. Pre-tests were given to all 30 subjects before to the six-week study period in order to evaluate the chosen physical factors. Post-tests were administered after the experimental period, and the results were carefully documented. A preset significance level of 0.05 confidence was used for the statistical analysis. The study's findings showed that individuals in the interval training with high intensity group significantly improved their muscle strength and agility.